Did the media support or subordinate women in the COVID-19 pandemic? An analysis of Turkish television commercials - Demirci, Kenan (IGI Global, 2022)
From the point of gender .studies, it is important to analyze the construction of women in the media and to determine the basic features of this construction. In this way, gender .studies aim to make requests for improvement by making comments on the media texts that are heavily consumed by people. From this perspective, the focus of this study is on the images of women in TV commercials during the COVID-19 pandemic in Turkey. In this context, the advertisements shot in 2020 and published on the YouTube video portal with the #evdehayatvar hashtag (there is life at home) were analyzed within the scope of the study. The analysis revealed that the positioning of women in private life and identification with the role of the mother in advertising continues to be an important trend in the design of women in advertising. © 2022, IGI Global. All rights reserved.